2008
DOI: 10.1111/j.1538-7836.2008.02837.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in patients with venous thromboembolism and hidden cancer: findings from the RIETE Registry

Abstract: VTE patients with hidden cancer have an increased incidence of recurrences, major bleeding or death during the first 3 months of therapy. With four simple, easily obtainable variables, it is possible to identify a subgroup of VTE patients with a higher risk for hidden cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 22 publications
3
28
1
2
Order By: Relevance
“…Except for rising age, which is a predictor for cancer diagnosis both after a first and recurrent VTE, we found anaemia to be a risk factor for a new cancer diagnosis after a first primary VTE in accordance to results by Trujillo-Santo et al [15]. Anaemia has also been shown to increase the risk of VTE after cancer diagnosis [16] further supporting this connection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Except for rising age, which is a predictor for cancer diagnosis both after a first and recurrent VTE, we found anaemia to be a risk factor for a new cancer diagnosis after a first primary VTE in accordance to results by Trujillo-Santo et al [15]. Anaemia has also been shown to increase the risk of VTE after cancer diagnosis [16] further supporting this connection.…”
Section: Discussionsupporting
confidence: 91%
“…This has not previously been shown. Ihaddadene et al [17] found no association between sex and occult malignancy, Sørenssen et al [10] found no particular gender difference and Trujillo-Santos et al [15] found an odds ratio of 1.3 for male sex but did not reach significance. The explanation for the increased risk of a cancer diagnosis associated with male sex found here is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 With respect to cancer, in adult patients who presented with VTE, malignancy was diagnosed in 1.2% to 4%. [43][44][45] This rate is not clearly reported in children, but most likely should be lower than in adults. This suggests other risks factors, such as mechanical obstruction, chemotherapy, and CVL, are significantly involved in the development of VTE in this population.…”
Section: Resultsmentioning
confidence: 72%
“…The spectrum of thrombotic episodes vary in severity, and these can present during or even prior to the diagnosis of cancer [2,3]. In a study of 17,475 patients with acute venous thromboembolism, 16% had a history of cancer, while hidden cancers were detected in 1.2% of patients [4].…”
Section: Introductionmentioning
confidence: 99%